Surgical resection of malignant tumors at the ischial tuberosity: a new surgical incision design and clinical experience - Cui, Haocheng; Zheng, Kai; Xu, Ming; Chen, Qian; Zhai, Kai; Yu, Xiuchun (Frontiers in Oncology, 2025)
ObjectiveThis study aims to present the anatomical characteristics of a novel surgical incision designed for single ischiectomy and to share our practical experience with its application.Methods and materialsThe newly developed surgical incision begins 5–6 cm below the posterior superior iliac spine and extends toward the ipsilateral greater trochanter, passing through the ischial tuberosity. It is then continued distally along the femur via the greater trochanter, forming what is referred to as a PIG-S incision. This study outlines the surgical resection procedures in two patients diagnosed with ischiotuberous chondrosarcoma who underwent surgery using the PIG-S incision. Key outcomes include surgical duration, intraoperative blood loss, and postoperative complications.ResultsIn one case, the patient experienced tumor recurrence nine months after an initial curettage of the ischial tubercle, necessitating complete tumor resection via the PIG-S approach. The second patient presented with ischiotuberous chondrosarcoma involving the lower margin of the acetabulum. A combined surgical approach using a PIG-S incision and an anterior ilioinguinal incision was adopted for tumor resection in regions II and III, with pelvic reconstruction performed using a 3D-printed prosthesis. The surgeries lasted for the two patients 90 and 150 min, with intraoperative blood losses of 1000 and 2000 mL, respectively. No postoperative incision-related complications were observed in either patient.ConclusionsThe PIG-S incision allows comprehensive exposure of crucial structures within the sciatic region, facilitates complete resection of the ischial tuberosity, and maximally preserves the sciatic nerve.